2019
DOI: 10.1097/md.0000000000018320
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid imaging reporting and data system combined with Bethesda classification in qualitative thyroid nodule diagnosis

Abstract: Objective: We aimed to investigate the value of the combined use of high-resolution ultrasound thyroid imaging reporting and data system (TI-RADS) classification and thyroid fine needle aspiration cytology (Bethesda classification) for the qualitative diagnosis of benign and malignant thyroid nodules. Methods: We enrolled 295 patients with 327 thyroid nodules who were scheduled to undergo thyroid nodule surgery. Before surgery, all the patients underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 32 publications
1
11
0
1
Order By: Relevance
“…The sensitivity of ACRTI-RADS for predicting the risk of malignancy was markedly higher than that seen in Brazil (90%) [15] Chile (88%) [14] China (77.3%) [19], Malaysia (85.7%) [22] Italy (67.6%) [29] and 58.9% [33], Israel 86% [13] and Turkey (76%) [34]. On the other hand a higher percentage of sensitivity was documented in different countries across the globe: Philippines (100%) [35], China (92.7%) [17] and (98.15%) [18], Korea (95.5%) [21] and (96.6%) [20] and Egypt (98.3%) [36]. In our study, the specificity of the ACRTI-RADS for predicting the risk of malignancy was lower than that reported in many different countries: obtained in Korea (58.6%) [21] and (52.9%) [20], Brazil (51.4%) [15], China (47.84%) [18] and (89.1%) [19], Philippines (52.2%) [36], Malaysia (51.1%) [22] and (70.7%) [17], Singapore (90.4%) [16], Italy (57.2 %) [29] and 58.9% [33], Egypt (90.9%) [36] and Turkey (97.5%) [34].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The sensitivity of ACRTI-RADS for predicting the risk of malignancy was markedly higher than that seen in Brazil (90%) [15] Chile (88%) [14] China (77.3%) [19], Malaysia (85.7%) [22] Italy (67.6%) [29] and 58.9% [33], Israel 86% [13] and Turkey (76%) [34]. On the other hand a higher percentage of sensitivity was documented in different countries across the globe: Philippines (100%) [35], China (92.7%) [17] and (98.15%) [18], Korea (95.5%) [21] and (96.6%) [20] and Egypt (98.3%) [36]. In our study, the specificity of the ACRTI-RADS for predicting the risk of malignancy was lower than that reported in many different countries: obtained in Korea (58.6%) [21] and (52.9%) [20], Brazil (51.4%) [15], China (47.84%) [18] and (89.1%) [19], Philippines (52.2%) [36], Malaysia (51.1%) [22] and (70.7%) [17], Singapore (90.4%) [16], Italy (57.2 %) [29] and 58.9% [33], Egypt (90.9%) [36] and Turkey (97.5%) [34].…”
Section: Discussionmentioning
confidence: 91%
“…Applying ACR TI-RADS criteria can minimize the number of ultrasound-guided FNACs performed on benign nodules [13]. Hence, many studies have assessed ACR TI-RADS to determine its sensitivity, specificity, positive predictive value, negative predictive value, accuracy rate and receiver operating characteristic (ROC) curves [14], [15], [16], [17], [18], [19], [20], [21], [22]. Thyroid ultrasound is a reliable non-invasive, practical method [6], [23]; it is accessible and has a low capital cost [6].…”
Section: Introductionmentioning
confidence: 99%
“…The adoption of an ultrasound (US) system for classifying thyroid nodules is useful for tailoring the diagnostic approach when evaluating these lesions and combining their workup with FNA biopsy [45][46][47][48]. Accurate categorization of thyroid nodules based on an US classification system, irrespective of whether it is the ACR-TIRADS or an alternative system, may help physicians in predicting their ROM and thus rationalize adequate management.…”
Section: Discussionmentioning
confidence: 99%
“…[11] In this study, FNA biopsy positive indicated thyroid cancer and the negative one indicated benign tumors. The thyroid imaging reporting and data system (TI-RADS) can perform standardized graded diagnosis of nodules [12]. Contrast-enhanced ultrasound is an advanced step from morphology to functional imaging.…”
Section: Discussionmentioning
confidence: 99%